Sport and non-specific low back pain in athletes: a scoping review - Fulvio Dal Farra; Federico Arippa; Giuseppe Carta; Marco Segreto; Elisa Porcu; Marco Monticone (BMC, 2022)
Abstract Background The contribution of sport in non-specific low back pain (NS-LBP) remains unknown, due to a large heterogeneity in the methods applied in research. The aims of this scoping review (ScR) were to systematically map and summarize findings concerning studies reporting data on NS-LBP among athletes. Methods This ScR was developed referring to the 2020 version of the "Joanna Briggs Institute Methodological Guidance" and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses for Scoping Reviews. Five medical databases (Pubmed, Cochrane, Central, Embase, Pedro and Scopus) were searched up to November 2021. No limitations in terms of study design and language were applied. Results were presented numerically and thematically. Results A total of 4061 records were identified through the initial search; 114 articles met the inclusion criteria. Publications have increased over the years, since 1990. Most of the studies were conducted in the USA (17.5%), even if most research was conducted in Europe (53.5%). Analytic observational (42%) and cross-sectional studies (37%) were the most used designs, followed by case reports (12%) and systematic reviews (9%). Boating (7%), football, soccer, volleyball, running and gymnastics (4.4% each) were the most investigated, although the majority of the studies considered sports in general (36.8%). The overall sample size median was 181, mean age 22 ± 10.2; 68% of athletes were professional and 32% amateur. Most of the studies (38%) did not detail the frequency of training. Sport was reported as a risk factor for developing NS-LBP in 67.5% of cases, especially in those studies which assessed activities implying high or repeated loading on the spine. Conclusions This is the first ScR to provide a comprehensive overview on this topic. The increased number of publications on the association between sport practice and NS-LBP demonstrates a growing interest over the years on this topic. Some sport activities seem to be more involved than others in LBP development; however, research methods are extremely varied, thus more standardized observational research may focus on specific disciplines to properly contribute to research and clinical practice.